Ketepatan Reasoning/Judgement dan Rekomendasi Mahasiswa Farmasi pada Kasus Vignette Swamedikasi Dispepsia - Jesica Mourin; Cecilia Brata (Keluwih)
Abstract—The public frequently comes to community pharmacies for self-medication to address mild symptoms, including dyspepsia. Pharmacy students need to develop appropriate clinical decision-making abilities to provide quality self-medication services as they prepare for their future roles as pharmacists. This study aims to describe the appropriateness of clinical reasoning/judgement and recommendations by pharmacy students in response to a vignette case of NSAID-induced dyspepsia. Data was collected through Google Form questionnaires, with third-year pharmacy students who currently took a course related to self-medication as participants. Descriptive statistics and inductive content analysis were used to analyze the data. The appropriateness of reasoning/judgement and recommendations was determined based on conformity with the literature and/or expert panel consensus. The total population was 162 students and of these 150 participated.  Of the 150 participants, 78% provided appropriate reasoning/judgement and recommendations to the NSAID-induced dyspepsia case. This showed that most pharmacy students at this university demonstrated correct clinical reasoning/judgment, and could provide appropriate recommendations for a case of NSAID-induced dyspepsia. This might imply that the changes in the Indonesian pharmacy curriculum, incorporating more clinical skills, have started showing positive effects.